2012
DOI: 10.7307/ptt.v23i2.135
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium-based Composite Materials in Construction of Transport Means

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…They observed that the mechanical properties were increases as the percentage contribution of SiC particles were increases. Milos et al [13] worked on the development of composite by Al5083 alloy reinforced with Al2O3 and graphite. The weight % and size of the reinforced particles was chosen as a variable to study the effect on mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that the mechanical properties were increases as the percentage contribution of SiC particles were increases. Milos et al [13] worked on the development of composite by Al5083 alloy reinforced with Al2O3 and graphite. The weight % and size of the reinforced particles was chosen as a variable to study the effect on mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…A proper selection of matrix & reinforcement and shape of the reinforcement is highly desirable for property improvement of the composite [7][8][9]. In recent years, aluminium and its alloys are most widely used non-ferrous metals and getting more popularity due to its high strength to weight ratio, easy to fabricate, and low production cost [10,11,12]. Aluminum metal matrix composites (AMMCs) reinforced with ceramic particles are simple & easy to process and also have the potential to give tailored property combinations [13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations where Al was reinforced by micro Al 2 O 3 with content ranging from 2050 wt-% showed a significant reduction in the Coefficient of Thermal Expansion (CTE) compared to unreinforced Al (Milos et al, 2011). Since the restriction effect of reinforcement particles causes CTE reduction, it is expected that using nanoparticles as reinforcements would even further reduce composite CTE.…”
mentioning
confidence: 99%